2012
DOI: 10.1371/journal.pone.0034551
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in the Prevalence of Overweight and Obesity in Sicilian Schoolchildren Aged 11–13 Years During the Last Decade

Abstract: The present study evaluates trends in the prevalence of overweight and obesity in relation to gender and area of residence between two cohorts of students aged 11–13 years in Sicily. The analysis was performed on 1,839 schoolchildren, with 924 and 915 children being studied in 1999–2001 and 2009–2010, respectively. The children who were enrolled during 2009–2010 had significantly higher body mass indexes (BMI), BMI z-scores, and waist circumferences than the children who were studied during 1999–2001 (p<0.0001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…Some other researchers reported similar findings (Deforche et al, 2009;Liou and Chiang, 2004). Furthermore, many studies reported that the prevalence of overweight and obesity among children and adolescents has increased dramatically in recent decades (Kovac et al, 2012;Livingstone, 2001;Moreno et al, 2000;Parrino et al, 2012;Tremblay and Willms, 2000;Wedderkopp et al, 2004;Ying-Xiu and Shu-Rong, 2012) and endurance and strength of children have decreased (Malina, 2007;Strel et al, 2007;Tomkinson and Olds, 2007). This suggests that current recommendations of at least 60 min of MVPA per day might be insufficient for preadolescent children to achieve optimal health benefits.…”
Section: Physical Activity Patterns In Urban 11-year-olds 197mentioning
confidence: 87%
“…Some other researchers reported similar findings (Deforche et al, 2009;Liou and Chiang, 2004). Furthermore, many studies reported that the prevalence of overweight and obesity among children and adolescents has increased dramatically in recent decades (Kovac et al, 2012;Livingstone, 2001;Moreno et al, 2000;Parrino et al, 2012;Tremblay and Willms, 2000;Wedderkopp et al, 2004;Ying-Xiu and Shu-Rong, 2012) and endurance and strength of children have decreased (Malina, 2007;Strel et al, 2007;Tomkinson and Olds, 2007). This suggests that current recommendations of at least 60 min of MVPA per day might be insufficient for preadolescent children to achieve optimal health benefits.…”
Section: Physical Activity Patterns In Urban 11-year-olds 197mentioning
confidence: 87%
“…6,23,46,62 Nevertheless, gender is a complex factor, controversially associated with overweight/ obesity trends. 13,16,20,45,63 In reference to that, and since both genders present high risk to obesity pathogenesis, boys and girls should be equally protected by its adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 There are several studies reporting an upward trend of childhood obesity over the years in several countries, like New Zealand, 7 USA, 8 Brazil, 9 China 10 and Taiwan. 11 This global trend has affected European countries too, 10,12,13 with the British islands and the countries in the Mediterranean region presenting the highest rates of overweight and obesity in pre-school age. 14 The increase in the prevalence of obesity is considered to be due to changes in environmental factors, such as poor nutrition 15 ; increase in the calorie intake and physical inactivity [16][17][18] ; prolonged television watching 19,20 ; working and playing on computer 20 ; family socioeconomic status 7,21,22 ; parental body mass index (BMI) 2,23,24 and parental separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses fatores impõem uma nova situação ao sistema nervoso central, gerando maior dificuldade nas atividades locomotoras 10 . A obesidade é um dos mais significativos problemas nutricionais da atualidade 11 e sua prevalência em crianças e adolescentes tem crescido no mundo 12,13 e no Brasil, onde Reis, Vasconcelos e Oliveira 14 mostraram que o excesso de peso tende a ser mais frequente no meio urbano do que no rural, em particular nas Regiões Norte, Nordeste e Centro-Oeste e que com magnitude menor, a prevalência da obesidade mostrou distribuição geográfica semelhante à observada para o excesso de peso.…”
Section: Introductionunclassified